2015
DOI: 10.1177/2047487314566758
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk in women with a history of spontaneous preterm delivery: A systematic review and meta-analysis

Abstract: Spontaneous preterm delivery is an independent risk factor for the development of IHD, stroke and overall CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 45 publications
2
54
0
2
Order By: Relevance
“…Accumulating evidence suggests that adverse pregnancy outcomes may serve as a screening test for future cardiovascular disease (CVD), the leading cause of morbidity and mortality in women . Prior studies report a 2‐ to 3‐fold increased risk of CVD in women with a history of PTB, even when not complicated by preeclampsia . In a record linkage study, severity and number of small‐for‐gestational‐age infants were associated with future maternal CVD‐related hospitalization or death (ie, coronary heart disease, cerebrovascular events, chronic heart failure) .…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that adverse pregnancy outcomes may serve as a screening test for future cardiovascular disease (CVD), the leading cause of morbidity and mortality in women . Prior studies report a 2‐ to 3‐fold increased risk of CVD in women with a history of PTB, even when not complicated by preeclampsia . In a record linkage study, severity and number of small‐for‐gestational‐age infants were associated with future maternal CVD‐related hospitalization or death (ie, coronary heart disease, cerebrovascular events, chronic heart failure) .…”
Section: Introductionmentioning
confidence: 99%
“…PTD has been found across numerous studies to be associated with CVD (Table ) . A meta‐analysis of 10 studies from various European countries showed that PTD was associated with a 38% increased risk of ischemic heart disease, 71% increased risk of stroke, and 2‐fold increased risk of overall CVD . Because preeclampsia and IUGR are common reasons for iatrogenic PTD and are each on their own associated with CVD risk, this meta‐analysis only included studies that excluded cases of preeclampsia or IUGR, or adjusted for hypertension/preeclampsia and birthweight.…”
Section: Preterm Deliverymentioning
confidence: 99%
“…[26][27][28][31][32][33][34] A meta-analysis of 10 studies from various European countries showed that PTD was associated with a 38% increased risk of ischemic heart disease, 71% increased risk of stroke, and 2-fold increased risk of overall CVD. 32 Because preeclampsia and IUGR are common reasons for iatrogenic PTD and are each on their own associated with CVD risk, this meta-analysis only included studies that excluded cases of preeclampsia or IUGR, or adjusted for hypertension/preeclampsia and birthweight. An analysis of the NHSII (Nurses' Health Study II) found that PTD was independently associated with a 42% greater risk of CVD after adjusting for prepregnancy lifestyle and CVD risk factors.…”
Section: Preterm Deliverymentioning
confidence: 99%
“…Also, abnormal angiogenic/anti-angiogenic profile in maternal plasma is seen in a subset of patients with spontaneous preterm birth [14], and increased resistance at midtrimester Doppler measurement of uterine artery flow provides an increased risk of spontaneous preterm birth [15]. In addition, women with a spontaneous preterm birth have an increased risk of developing cardiovascular disease later in life [16, 17]. These findings suggest an overlap with other ischemic placental diseases such as preeclampsia.…”
Section: Introductionmentioning
confidence: 99%